The Early Antibody-Dependent Cell-Mediated Cytotoxicity Response Is Associated With Lower Viral Set Point in Individuals With Primary HIV Infection - Chen, Xi; Lin, Meilin; Qian, Shi; Zhang, Zining; Fu, Yajing; Xu, Junjie; Han, Xiaoxu; Ding, Haibo; Dong, Tao; Shang, Hong; Jiang, Yongjun (Frontiers in Immunology, 2018)
Antibody-dependent cell-mediated cytotoxicity (ADCC) is an immune response largely mediated by natural killer (NK) cells that can lyse target cells and combat tumors and viral infections. However, the role of ADCC in response to primary HIV infection is poorly understood. In the present study, we explored the ADCC response and evaluated its characteristics in 85 HIV-infected individuals, including 42 with primary infections. Our results showed that ADCC occurs during acute infection, and the earliest ADCC response to a single peptide was detected at 52 days. Primary HIV-infected individuals exhibiting ADCC responses had lower viral set points than those with no ADCC response, and functional analyses demonstrated that the ADCC response could significantly inhibit viral infection during primary HIV infection. HIV epitopes that provoked the ADCC response were determined and three relatively conserved epitopes (HNVWATYACVPTDPNPQE, TSVIKQACPKISFDPIPI and VVSTQLLLNGSLAEEEII) from the surface of the three-dimensional structure of the HIV Env protein were identified. Overall, our data indicate that ADCC responses may be significant for the control of HIV from an early stage during infection. These findings merit further investigation and will facilitate improvements in vaccines or therapeutic interventions against HIV infection.